Boosting activity toward oxygen reduction reaction of a mesoporous FeCuNC catalyst via heteroatom doping-induced electronic state modulation. Issue 10 (14th February 2022) - Kim, Jong Gyeong; Cho, Jinwon; Han, Sunghoon; Lee, Hyejin; Yuk, Eunsung; Bae, Byungchan; Jang, Seung Soon; Pak, Chanho
Abstract : Mesoporous Fe and Cu anchored in N-, S-, and P-doped carbon (FeCu x NC) catalysts, revealing the presence of ordered mesoporous grain-shaped particles and demonstrating that the electronic state of the active sites (Fe–N x ) is controlled by their environments, which can affect ORR kinetics. Abstract : Non-precious metal catalysts for oxygen reduction reaction (ORR) are promising alternatives to Pt/C in fuel cells, thus, demand for advanced catalysts is arising. Herein, we prepared and characterized mesoporous Fe and Cu anchored in N-, S-, and P-doped carbon (FeCu x NC) catalysts, revealing the presence of ordered mesoporous grain-shaped particles and demonstrating that the electronic state of the active sites (Fe–N x ) is controlled by their environments, which can affect ORR kinetics. Half-cell measurements revealed that FeCu x NC promoted ORRs more effectively (0.92 V at 3 mA cm −2 ) than Pt/C (0.87 V at 3 mA cm −2 ) in alkaline conditions, while a current density of 490 mA cm −2 was achieved at 0.6 V in a single-cell level. Multi-heteroatom doping modulated the energy of OOH* and OH − adsorption on the active sites, and the lowest overpotential (according to density functional theory calculations) was obtained for the Fe–Cu–N3 –C–P–S model.